Transformasi Pembelajaran Digital bagi Generasi Muda: Studi Kasus Pelatihan Microsoft Word di MTS Pembangunan - Abdullah Ardi; Yazid Aufar (Jurnal Pengabdian Masyarakat Nusantara, 2025)
Digital learning transformation has become an essential need in the era of Industry 4.0, particularly for younger generations with limited access to technology. This community service program was carried out to address the lack of ICT subjects and limited computer literacy among students at MTS Pembangunan. The training, conducted by lecturers from the Informatics Engineering Department of Politeknik Hasnur, employed the Discussion Group Learning (DGL) method an approach that combines group discussions with hands-on practice. A total of 78 students from grades VII to IX participated in the training, which focused on basic Microsoft Word functions such as text formatting, table creation, and image insertion. The evaluation results revealed that 96.2% of students successfully completed the practical tasks, and the session was marked by active engagement and high enthusiasm. These outcomes demonstrate that well-structured yet simple training using participatory methods can significantly improve students' digital literacy. This finding reinforces the importance of applying active learning methods to empower young people with digital skills, preparing them for future educational and professional challenges.